(untitled) (AmS-Skrifter, 2019)
In recent years, a number of early Christian cemeteries have been excavated in the region of Skagafjörður, North Iceland. They belonged to, and were managed by, occupants of individual farms and were in use from around AD 1000-1120. These household cemeteries differ from the sparse pagan burial record in that they are ‘all inclusive’, i.e. they include individuals of both sexes and all ages, and essentially represent all inhabitants of a household. An interesting feature of the cemeteries is the large number of interred infants and relatively large number of ‘older’ individuals. By looking at the osteological data in conjunction with the placement of burials within cemeteries a more detailed picture of the Medieval household emerges, including the perception of the young and the aged and the possible role of three-generation families in the transference of knowledge and life experience. This paper discusses how this unique material can add to the predominantly philological and historical discussions on the nature, composition and social interactions of the Medieval Icelandic household.